2018
DOI: 10.1038/nrneph.2017.169
|View full text |Cite
|
Sign up to set email alerts
|

Novel treatment strategies for chronic kidney disease: insights from the animal kingdom

Abstract: Many of the >2 million animal species that inhabit Earth have developed survival mechanisms that aid in the prevention of obesity, kidney disease, starvation, dehydration and vascular ageing; however, some animals remain susceptible to these complications. Domestic and captive wild felids, for example, show susceptibility to chronic kidney disease (CKD), potentially linked to the high protein intake of these animals. By contrast, naked mole rats are a model of longevity and are protected from extreme environme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
101
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 85 publications
(104 citation statements)
references
References 283 publications
(237 reference statements)
2
101
0
1
Order By: Relevance
“…The consequence of such prolong intensive support is loss of bone and muscle mass and eventual organ failure. These features are not observed in hibernating mammals, such as the brown bear , which is able to preserve muscle and bone mass during several months of hibernation. Critical to this is a dynamic microbiome .…”
Section: Animal Models For Microbiome and The Diseasome Of Ageingmentioning
confidence: 91%
See 1 more Smart Citation
“…The consequence of such prolong intensive support is loss of bone and muscle mass and eventual organ failure. These features are not observed in hibernating mammals, such as the brown bear , which is able to preserve muscle and bone mass during several months of hibernation. Critical to this is a dynamic microbiome .…”
Section: Animal Models For Microbiome and The Diseasome Of Ageingmentioning
confidence: 91%
“…Of note, mammalian longevity shows a strong negative correlation with nutritionally acquired serum phosphate levels . Indeed, human progerias, such as Hutchinson's Guilford's syndrome, or a disease of accelerated ageing, such as CKD, display elevated serum phosphate levels . Epidemiological studies have indicated that frequent consumption of red meat is a source of age‐related hyperphosphataemia in man .…”
Section: The Ageing Processmentioning
confidence: 99%
“…Nrf‐1 transcription is regulated also by PPAR‐β in muscle of exercised rats, a mechanism that increases MB through upregulation of AMP‐activated protein kinase (AMPK) and Nrf‐1/Nrf‐2 that integrate their effects on the nuclear genes of MB with promotion of the replication and transcription of TFAM. The latter is a multifunctional protein that belongs to the high‐mobility group (HMG) proteins that are characterized by their ability to bend, wrap and unwind mtDNA without sequence specificity, but with preferential interaction with some identified regions …”
Section: Mitochondria Physiologymentioning
confidence: 99%
“…The latter is a multifunctional protein that belongs to the high-mobility group (HMG) proteins that are characterized by their ability to bend, wrap and unwind mtDNA without sequence specificity, but with preferential interaction with some identified regions. 18,[21][22][23] Tumour suppressor protein p53 is known as the "guardian of the mitochondria genome" 24 and has the ability to modulate expression of both the mitochondrial and the nucleus genes. 25,26 Metabolic stress results in p53 activation by its key modulator PGC-1α and triggers cell-cycle arrest, reactive oxygen species (ROS) clearance or apoptosis.…”
Section: Mitochondrial Biogenesismentioning
confidence: 99%
“…However, life expectancy estimates for 330 animal species exist, based on data from North American Zoos and aquariums . Although the size of the animal has been considered, a main factor that determine longevity a number of other factors, such as telomere shortening rate , resting heart rate , DNA repair capacity , protein methionine tissue content and serum phosphate levels correlates to species lifespan. Studies of animal species that exhibit a high longevity quotient (actual longevity/expected longevity), negligible senescence and superior resistance to age‐related diseases, such as naked mole rats ( Heterocephalus glaber ) , little brown bats ( Myotis brandtii ) , ocean quahog ( Arctica Icelandica ) , rockfish ( Sebastes ) , bowheads whale ( Balaena mysticetus ) and Greenland shark ( Somniosus microcephalus ) are of special interest for biomimetic studies since they have adapted beneficial changes during evolution that make them exceptionally long‐lived .…”
Section: Longevity In the Animal Kingdom – Novel Insights Benefit Germentioning
confidence: 99%